2017
DOI: 10.1111/bjh.14863
|View full text |Cite
|
Sign up to set email alerts
|

Application of whole‐exome sequencing to direct the specific functional testing and diagnosis of rare inherited bleeding disorders in patients from the Öresund Region, Scandinavia

Abstract: SummaryRare inherited bleeding disorders (IBD) are a common cause of bleeding tendency. To ensure a correct diagnosis, specialized laboratory analyses are necessary. This study reports the results of an upfront diagnostic strategy using targeted whole exome sequencing. In total, 156 patients with a significant bleeding assessment tool score participated in the study, of which a third had thrombocytopenia. Eighty‐seven genes specifically associated with genetic predisposition to bleeding were analysed by whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 49 publications
5
69
1
Order By: Relevance
“…This detection rate is in keeping with other recent previous large‐scale targeted panel sequencing studies and the application of WES to patients with IT of unknown etiology 4 , 12 , 20 , 21 . One possible explanation for the inflated detection rate for panel based platforms is the relative increase in average read coverage when compared to WES analysis, especially at the point of variation.…”
Section: Discussionsupporting
confidence: 88%
“…This detection rate is in keeping with other recent previous large‐scale targeted panel sequencing studies and the application of WES to patients with IT of unknown etiology 4 , 12 , 20 , 21 . One possible explanation for the inflated detection rate for panel based platforms is the relative increase in average read coverage when compared to WES analysis, especially at the point of variation.…”
Section: Discussionsupporting
confidence: 88%
“…The use of whole exome sequencing in the diagnosis of inherited bleeding disorders (IBD) has the potential to identify pathogenic genetic variants already associated with well‐defined bleeding disorders. Recent studies have identified novel defects in collagen genes in patients with IBD . This highlights the importance of including an evaluation of collagen defects in a comprehensive evaluation of patients with bleeding disorders.…”
Section: Bleeding and Bruising In The Hypermobile Patientmentioning
confidence: 97%
“…Since 2013, we have implemented WES as an upfront diagnostic method to diagnose patients suspected of inherited bleeding disorders, enabling a continuous update of novel discovered genes to be analysed. Following our recent publication (Leinoe et al , ), we have expanded the downstream specific testing guided by genetic results to include immunofluorescence microscopy, thrombopoietin level and CD34 expression on platelets. Since some IT may be caused by CNV, we validated a tool for CNV calling from WES data.…”
Section: Listing Positive Diagnosis Of 33 Patients the Variant In C3mentioning
confidence: 99%